2021
DOI: 10.1155/2021/9965737
|View full text |Cite
|
Sign up to set email alerts
|

TRPV1 Channel Activated by the PGE2/EP4 Pathway Mediates Spinal Hypersensitivity in a Mouse Model of Vertebral Endplate Degeneration

Abstract: Low back pain (LBP) is the primary cause of disability globally. There is a close relationship between Modic changes or endplate defects and LBP. Endplates undergo ossification and become highly porous during intervertebral disc (IVD) degeneration. In our study, we used a mouse model of vertebral endplate degeneration by lumbar spine instability (LSI) surgery. Safranin O and fast green staining and μCT scan showed that LSI surgery led to endplate ossification and porosity, but the endplates in the sham group w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 66 publications
0
5
0
1
Order By: Relevance
“… 219 Activation of the TRPV1 channel by the PGE2/EP4 cell signaling pathway induces spinal hypersensitivity in a mouse model of CEP degeneration. 220 …”
Section: Ivdd and How It Contributes To The Generation Of Di...mentioning
confidence: 99%
See 1 more Smart Citation
“… 219 Activation of the TRPV1 channel by the PGE2/EP4 cell signaling pathway induces spinal hypersensitivity in a mouse model of CEP degeneration. 220 …”
Section: Ivdd and How It Contributes To The Generation Of Di...mentioning
confidence: 99%
“…The reduced osmolarity in the degenerate IVD due to depletion of aggrecan increases TRPV4 expression and pro‐inflammatory cytokine production by IVD cells 219 . Activation of the TRPV1 channel by the PGE2/EP4 cell signaling pathway induces spinal hypersensitivity in a mouse model of CEP degeneration 220 …”
Section: Ivdd and How It Contributes To The Generation Of Discogenic Lbpmentioning
confidence: 99%
“…PGE2/EP4 pathway-induced activation of the transient receptor potential cation channel subfamily V member 1 (TRPV1) may be another subchondral bone homeostasis and osteoarthritis pain mechanism. A previous study has shown that the PGE2/EP4 pathway leads to the activation of the TRPV1 channel, further inducing spinal hypersensitivity and spinal pain in the DRG neurons of lumbar spine instability mice [ 48 ]. In addition, the activation of the TRPV1 channel, induced by zoledronic acid, promotes osteoblast mineralization [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…PGE2 is also involved in pain processes in diseases such as osteoarthritis and rheumatoid arthritis [166] . For patients with low back pain, the increase in PGE2 in the porous endplate stimulates sensory nerves, leading to spinal cord pain [167] , [169] . The use of low-dose celecoxib can inhibit endplate porosity, sensory innervation, as well as spinal pain and allergies [170] .…”
Section: Pathophysiological Mechanisms Underlying Acute Bone Loss Aft...mentioning
confidence: 99%